The chemistry of κ2-N, S-chelated Ru(II) complexes with 1, 4-diethynylbenzene. (15th November 2022) - Afsan, Zeenat; Ahmad, Asif; Zafar, Mohammad; Das, Arpita; Roisnel, Thierry; Ghosh, Sundargopal
Graphical abstract: Reactions of both Cp* and borated-based κ 2 - N, S -chelated Ru(II) complexes have been carried out with 1, 4-diethynyl benzene that led to the formation of hydrotrisborate ruthenium species and alkyne inserted ruthenium alkenyl complexes. Abstract: The chemistry of κ 2 -N, S -chelated Ru(II) complexes, [Cp*RuPPh3 ( κ 2 - N, S -(NC7 H4 S2 )] (Cp*=ƞ 5 -C5 Me5 ), 1a and [PPh3 { κ 2 -N, S -(NS2 C7 H4 )}Ru{ κ 3 -H, S, S-H2 B(NC7 H4 S2 )2 }], 1b has been explored with a terminal alkyne 1, 4-diethynylbenzene. For example, the room-temperature reaction of Cp* based κ 2 - N, S -chelated Ru(II) species 1a with 1, 4-diethynyl-benzene yielded [RuCp*( κ 1 - N, S -C7 H4 NS2 )C7 H4 NS2 -(E)-N−C=CHC8 H5 ], 2 . On the other hand, although treatment of 1b with 1, 4-diethynylbenzene at room temperature showed no reactivity, thermolysis led to the formation of two borate complexes, [PPh3 {C7 H4 NS2 -( E )-N−C=CHC8 H5 }Ru{ κ 3 -H, S, Sʹ-H2 B(C7 H4 NS2 )2 }], 3 and [PPh3 ( κ 2 - N, S -C7 H4 NS2 ) Ru{ κ 3 -S, Sʹ, Sʹʹ-HB(C7 H4 NS2 )3 }], 4, albeit in poor yields. Both the Ru(II) species 2 and 3 contain a five-membered ruthenacycle with an exocyclic C=C moiety attached to carbon atom. In complex 4, the ruthenium center is stabilized by hydrotrisborate, phosphine, and hemilabile one N, S -chelating ligand. The key feature of 4 is the coordination of the boron atom to the metal center through a common sulphur atom of the 2-mercaptobenzothiazole ligand. Characterization of these Ru(II) species has been carried out by various spectroscopic techniques and single-crystal X-ray diffraction analysis for 4 . In addition, Density Functional Theory (DFT) calculations were further performed to provide insight into the bonding and electronic structures of these complexes.